On Periodically Potent Places: The Theatre Stage as a Temporarily Empowered Space for Ritual Performances in Cambodia. Issue 5 (20th October 2017) - Khoury, Stéphanie
Abstract : In this paper, I aim to discuss the notion of potency as attributed or inherent to a place through the study of the performance space in which the Khmer ritual classical theatre is staged. Here, the potency of the place results from a complex and cumulative process that strengthens the rite. Through a deliberately identified topography, a space is delimited, constructed and periodically activated so a community can safely transit from one yearly cycle to the next. In so doing, the ritual performance highlights nuanced qualities as well as social and religious considerations of space, and its relation to power. Considering the location's contribution to the rite helps not only to discuss the relation of people to space but also brings greater understanding to performance as a religious expression.